Mathematical framework for accurate prayer times: Insights from the bencet tradition - Muhaimin, Lukman Hakim; Kusumah, Yaya S.; Juandi, Dadang; Hendriyanto, Agus; Sahara, Sani (Universitas Islam Negeri Raden Intan Lampung, 2023)
Mathematics is fundamental in structuring religious practices, especially in determining prayer times. This study explores the mathematical concepts embedded in the traditional bencet tool used by communities to calculate prayer times accurately. Using a qualitative ethnographic approach, the research examines both the use and crafting of bencet through observations, interviews, and documentation. Based on the Miles and Huberman model, data analysis reveals that the bencet tongkat unconsciously incorporates mathematical concepts such as parallel lines, measurements, and planar surfaces. Similarly, the bencet garis reflects understanding parallel and perpendicular lines, circular constructions for 90° angles, and precise measurements. The findings underscore the deep interconnection between mathematical principles and cultural traditions. This study concludes that the bencet tool represents an untapped resource for ethnomathematics research. The implications highlight the potential of ethnomathematics as an innovative approach to mathematics education, integrating cultural heritage into learning.